I could find the role of Striling Numbers in the natural logarithm function as follows

$$x\log(x)=(\frac{x-1}{x})+\frac{3}{2!}(\frac{x-1}{x})^2+\frac{11}{3!}(\frac{x-1}{x})^3+...\frac{S_{n}}{n!}(\frac{x-1}{x})^n$$ Where $S_n$= absolute Striling Numbers of first kind (0,1,3,11,50,274....)

this series numerically checked without any problem, but I need the proving. Any help?


$$\log(1-x)=-\sum_{n=1}^\infty \frac{1}{n}x^n$$ so $$\log(x)=-\log\frac{1}{x}=-\log(1-\frac{x-1}{x})=\sum_{n=1}^\infty \frac{1}{n}(\frac{x-1}{x})^n$$ And $$\frac{1}{1-x}=\sum_{n=0}^\infty x^n$$ so $$x=\frac{1}{1-\frac{x-1}{x}}=\sum_{n=0}^\infty (\frac{x-1}{x})^n$$

and thus

$$x\log(x)=(\sum_{n=1}^\infty \frac{1}{n}(\frac{x-1}{x})^n)\cdot \sum_{m=0}^\infty (\frac{x-1}{x})^m = \sum_{n=1}^\infty a_n(\frac{x-1}{x})^n$$ where $$a_n=\sum_{k=0}^{n-1} \frac{1}{n-k}=1+\frac{1}{2}+\frac{1}{3}+....\frac{1}{n}=\frac{S_n}{n!}$$

So the result is $$x\log(x)=\sum_{n=1}^\infty \frac{S_n}{n!}(\frac{x-1}{x})^n$$


we will need the fact that $$n!H_n = n!\left(1+\frac{1}{2}+\frac{1}{3}+\cdots+\frac{1}{n} \right) = S(n,2)\\ \text{ where } S(n,2) \text{ is the Stirlings number of the first kind}$$

let me make a change of variable $u= \dfrac{x-1}{x}, x = \dfrac{1}{1-u}.$ then

$\begin{align} x\ln x &= \dfrac{1}{1-u} \ln \left(\dfrac{1}{1-u}\right) = -\dfrac{1}{1-u} \ln (1-u)\\ &=\left(1+u+u^2 + \cdots\right)\left(u+\frac{u^2}{2}+\frac{u^3}{3} + \cdots\right)\\ &=u+(\frac{1}{2}+1)u^2+(\frac{1}{3}+\frac{1}{2}+1)u^3+(\frac{1}{4}+\frac{1}{3} + \frac{1}{2}+1)u^4+\cdots\\ &=u+H_2u^2+H_3u^3+H_4u^4+\cdots\\ &=u+\frac{S(2,2)}{2!}u^2+\frac{S(3,2)}{3!}u^3+\frac{S(4,2)}{4!}u^4+\cdots +\frac{S(n,2)}{n!}u^n+\cdots\\ \end{align}$


We have

$$x\log(x) = x[-\log(1/x)] = x\left[-\log\left(1 - \frac{x-1}{x}\right)\right] = x\sum_{m = 0}^\infty \frac{1}{m+1}\left(\frac{x-1}{x}\right)^{m+1},$$

and $$x = \dfrac{1}{\frac{1}{x}} = \dfrac{1}{1 - \frac{x-1}{x}} = \sum_{m = 0}^\infty \left(\frac{x - 1}{x}\right)^m.$$ Thus

$$x\log(x) = \sum_{m = 0}^\infty \left(\frac{x-1}{x}\right)^m \sum_{m = 0}^\infty \frac{1}{m}\left(\frac{x-1}{x}\right)^m = \sum_{m = 0}^\infty \sum_{k = 0}^m \frac{1}{k+1}\left(\frac{x-1}{x}\right)^{m+1},$$

which is the same as $$\sum_{m = 0}^\infty \frac{S_m}{m!}\left(\frac{x-1}{x}\right)^{m+1}$$


Suppose we seek to show that $$x\log x = \sum_{n=1}^\infty \frac{1}{n!} \left[n+1\atop 2\right] \left(\frac{x-1}{x}\right)^n.$$

Recall the species equation for decompositions into disjoint cycles: $$\mathfrak{P}(\mathcal{U}\mathfrak{C}(\mathcal{Z}))$$ which gives the generating function $$G(z, u) = \exp\left(u\log\frac{1}{1-z}\right)$$ so that $$\left[n+1\atop 2\right] = \frac{1}{2} (n+1)! [z^{n+1}] \left(\log\frac{1}{1-z}\right)^2.$$

Substitute this into the sum to get $$\frac{1}{2} \sum_{n=1}^\infty \frac{1}{n!} (n+1)! \left(\frac{x-1}{x}\right)^n [z^{n+1}] \left(\log\frac{1}{1-z}\right)^2 \\ = \frac{1}{2} \sum_{n=1}^\infty (n+1) \left(\frac{x-1}{x}\right)^n [z^{n+1}] \left(\log\frac{1}{1-z}\right)^2.$$

Now $\left(\log\frac{1}{1-z}\right)^2$ starts at $z^2$ so that we may include the value for $n=0$ in the sum (zero contribution) to get $$\frac{1}{2} \sum_{n=0}^\infty (n+1) \left(\frac{x-1}{x}\right)^n [z^{n+1}] \left(\log\frac{1}{1-z}\right)^2.$$

What we have here is an annihilated coefficient extractor that evaluates to $$\frac{1}{2} \left. \frac{d}{dz} \left(\log\frac{1}{1-z}\right)^2 \right|_{z=(x-1)/x}.$$ This is $$\left. \frac{1}{1-z} \log\frac{1}{1-z} \right|_{z=(x-1)/x}$$ which finally yields $$\frac{1}{1-(x-1)/x} \log\frac{1}{1-(x-1)/x} = \frac{x}{x-(x-1)} \log\frac{x}{x-(x-1)} \\ = x \log x.$$

There is another annihilated coefficient extractor at this MSE link I and another one at this MSE link II and at this MSE link III.


Admittedly the same is done in one form or another in previous answers, I just wanted to make it as concise as possible.

Substituting $x=\frac1{1-y}$, what we have to prove is$$(1+y+...+y^n+...)(y+\frac{y^2}2+...+\frac{y^n}n+...)=y+\frac3{2!}y^2+...+\frac{S_n}{n!}y^n+...,$$i. e. $n!(1+\frac12+...+\frac1n)=S_n$.

Now what you denote by $S_n$ is usually denoted $|s(n+1,2)|$ or $\left[\matrix{n+1\\2}\right]$, and the needed equality is explicitly given e. g. in Wikipedia.

Just for fun, here is a quick combinatorial proof. By definition $S_n$ is the number of permutations of $n+1$ consisting of exactly two (disjoint) cycles. To name such a permutation means to name a subset of $\{1,...,n+1\}$ of size, say, $k$, with $0<k<n+1$, together with cyclic ordering of this subset and of its complement.

Now the number of subsets of size $k$ is $\binom{n+1}k$, while the number of cyclic orderings of a set of size $\ell$ is $(\ell-1)!$, so we get $\binom{n+1}k(k-1)!(n-k)!=\frac{(n+1)!}{k(n+1-k)}=n!\left(\frac1k+\frac1{n+1-k}\right)$. We then have to sum over $1\le k\le n$ and divide by 2 (since we have counted each disjoint pair of cycles twice, first at $k$ and then at $n+1-k$). The result is $n!H_n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.